2020
DOI: 10.1186/s12888-020-02898-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nurses’ experiences of psychological distress during care of patients with COVID-19: a qualitative study

Abstract: Background COVID-19 infection is a new disease that infects a large number of people, killing a ratio of whom every day in the world. Healthcare staff, especially nurses, experience a great deal of psychological distress during care of COVID-19 patients. Detecting factors that disturb nurses’ mental health during care of these patients can help to reduce their psychological distress. Therefore, this study aimed to explore nurses’ experiences of psychological distress during care of patients with COVID-19. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
371
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(474 citation statements)
references
References 33 publications
(62 reference statements)
40
371
0
16
Order By: Relevance
“…On the one hand, overwhelming, ambiguity feelings, feeling helpless, feelings of pointlessness, guilt, and remorse, losing control, and a sense of providing futile care were identified when health professionals fought against events such as unprecedent heavy workload, depletion of existing human resources, shortage in protective devices, or patients die despite hard work. Other feelings also included anxiety against the death, anxiety due to the nature of an unknown virus, anxiety caused by corpse burial, fear of infecting the family, distress about time wasting, distress of always delivering bad news, fear of being contaminated, the emergence of obsessive thoughts, and the bad feeling of wearing PPE [ 13 ]. On the other hand, positive feelings including conscientiousness and self-sacrifice for patients were also identified when healthcare professionals risking their health and lives for their patients and being loyal to the medical oath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, overwhelming, ambiguity feelings, feeling helpless, feelings of pointlessness, guilt, and remorse, losing control, and a sense of providing futile care were identified when health professionals fought against events such as unprecedent heavy workload, depletion of existing human resources, shortage in protective devices, or patients die despite hard work. Other feelings also included anxiety against the death, anxiety due to the nature of an unknown virus, anxiety caused by corpse burial, fear of infecting the family, distress about time wasting, distress of always delivering bad news, fear of being contaminated, the emergence of obsessive thoughts, and the bad feeling of wearing PPE [ 13 ]. On the other hand, positive feelings including conscientiousness and self-sacrifice for patients were also identified when healthcare professionals risking their health and lives for their patients and being loyal to the medical oath.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al described the experience of twenty nurses and reported an evolution from negative to positive emotions during the first outbreak [ 12 ]. Similarly, Galehdar et al described that nurses attending COVID-19 patients experienced a variety of psychological distress during the first outbreak [ 13 ]. Most qualitative studies have been conducted in a specific healthcare population, nursing.…”
Section: Introductionmentioning
confidence: 99%
“…The following two hypotheses and one research question were formulated. First, previous studies showed that being close to people infected with COVID-19 would increase psychological distress, higher anxiety, and avoidance behavior [ 17 , 18 , 27 ]; accordingly, we expected that being close to people infected with COVID-19 would be associated with higher health anxiety. Second, others have shown that hospital staff members working on the frontline reported higher symptoms of distress and anxiety [ 12 , 13 ]; given this, we anticipated that working on the frontline would be associated with higher scores for health anxiety and trait and state anxiety.…”
Section: Introductionmentioning
confidence: 96%
“…A higher task load was associated with lower general health [ 16 ]. In addition, frontline nurses reported anxieties related to the disease, fear of infecting their families, emotional distress related to delivering bad news, and conflicts between (dysfunctional) fears and the need to discharge a vital job [ 17 ]. Of 761 nurses surveyed in one study, 267 reported fear of getting infected [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 The expected combined action of the government and the public to follow health instructions and to stay at home can reduce the disease spread and the workload of health workers and professionals and improve their mental health and distress them. 12 Further, a specific Pre-holiday season policy or program that caters the physical, 9 mental 2 and spiritual 3 needs of the healthcare workers and professionals in the Philippines is suggested.…”
mentioning
confidence: 99%